Gel electrophoresis and hybridization of DNA-functionalized quantum-dots as part of a study of linear quantum-dot chains - Oda Masaru; Sasano Kosuke; Nishi Akira; Zako Tamotsu; Tani Toshiro (EPJ Web of Conferences, 2018)
We report the results of our investigation of agarose gel electrophoresis and hybridization of mercaptopropionic-acid-capped quantum dots (MPA-capped QDs) conjugated with short single-stranded DNA, as part of a study of closely spaced linear QD chains. The electrophoresis results suggest that migration speed and separation resolution depend on the amount of MPA on the QD surface. The QDs separated by electrophoresis according to DNA valence, i.e., the amount of DNA per particle, were used as building blocks for the synthesis of linear QD oligomers.